2021
DOI: 10.9734/jammr/2021/v33i2331198
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Year Review of Caesarean Section at the Rivers State University Teaching Hospital, South-South, Nigeria

Abstract: Background: Caesarean section (CS) is a major obstetric surgery done for pregnant women and is lifesaving.  Aim: The study was aimed at reviewing CS at the Rivers State University Teaching Hospital (RSUTH), to determine the prevalence, trend and indications, for improved management outcomes. Methods: In this cross-sectional study, we reviewed five thousand, five hundred and ninety-eight (5598) cases of caesarean sections (3699 emergency, 1899 planned) managed at the RSUTH from 1st January, 2015 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Based on facility-type, tertiary facilities were the most dominant study settings (80.0%) among the included studies in our review. However, we found the reported prevalence rates in tertiary facilities (5.5–56.5%) to be broadly comparable with the prevalence rates in secondary facilities (5.4–37.7%), with only nine [ 23 , 25 , 39 , 46 , 49 , 52 , 53 ] of the 70 tertiary facilities included in the review recording intra-facility CS rates greater than the range observed in secondary facilities. A similar pattern of comparable intra-facility CS prevalence in secondary (10.1% (95% CI: 5.1, 16.6%)) and tertiary hospitals (15.4% (95% CI: 12.5, 18.6%)) was reported in a Cameroonian systematic review [ 75 ].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Based on facility-type, tertiary facilities were the most dominant study settings (80.0%) among the included studies in our review. However, we found the reported prevalence rates in tertiary facilities (5.5–56.5%) to be broadly comparable with the prevalence rates in secondary facilities (5.4–37.7%), with only nine [ 23 , 25 , 39 , 46 , 49 , 52 , 53 ] of the 70 tertiary facilities included in the review recording intra-facility CS rates greater than the range observed in secondary facilities. A similar pattern of comparable intra-facility CS prevalence in secondary (10.1% (95% CI: 5.1, 16.6%)) and tertiary hospitals (15.4% (95% CI: 12.5, 18.6%)) was reported in a Cameroonian systematic review [ 75 ].…”
Section: Discussionsupporting
confidence: 51%
“…Also, 82.2% of the included studies were conducted in public [ 21 38 , 40 , 42 , 44 – 55 , 57 , 58 , 60 – 62 , 64 , 65 ] and 80.0% were conducted in tertiary [ 21 – 40 , 42 , 44 – 47 , 49 55 , 57 , 58 , 60 – 62 , 65 ] facilities. Also, 32 (71.1%) studies [ 21 – 44 , 58 – 64 ] were conducted between 2000 and 2014 (pre-WHO CS statement), while eight (17.8%) studies [ 45 52 ] were conducted after the WHO statement was published (i.e., from 2015). The remaining five (11.1%) studies [ 53 – 57 ] had their study periods overlapping both timeframes (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation